Singapore's sovereign wealth funds : the political risk of overseas investments - Wu, Friedrich (2009)
This paper seeks to examine Singapore's two sovereign wealth funds (SWFs)-the Government Investment Corporation of Singapore (GIC) and Temasek Holdings (Temasek)-and the political risks which they are exposed to in their overseas investments. We argue that Temasek has hitherto exposed itself to a greater level of political risk than GIC, but is in turn rewarded with a higher rate of returns on its investments. At the same time, we find that political risk is an inevitable challenge for SWFs in general. In fact, as worldwide opinion has turned towards demanding for greater transparency and accountability from SWFs, the political risks faced by SWFs have correspondingly risen. This paper seeks to throw some light on this issue by undertaking a case study of Singapore's two SWFs, which are consistently ranked among the global top 10 SWFs by assets, and have attracted much worldwide attention in recent times as a result of their politically-controversial overseas investments.